INNOVATIVE INNOVATIONS IN THE FIELD OF EDUCATION (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Innovation in education plays an important role in the development of modern society. The development and improvement of the educational system is carried out through the use of new methods and technologies. These innovations not only serve to make the learning process more effective, but also make it possible to improve the quality of education, improve the knowledge and skills of students. Currently, innovative approaches are widely used at all stages of education, from school to higher education